THERAPEUTIC EVALUATION OF CENTELLA ASIATICA MACERATE ON SURGICAL COMPLICATIONS OF OVARIOHYSTERECTOMY IN THE BITCH - SOROMOU, Lanan Wassy; Lolahara, Gobou; KPOULOMOU, Cécé (Universal Journal of Pharmaceutical Research, 2024)
Background and objectives: The management of post-operative complications such as severe inflammatory reactions, suture dehiscence and abdominal hernia in farm animals calls for a variety of practices, including the use of plant resources. The aim of this study is to explore practices for managing surgical complications in bitches and the healing properties of Centella asiatica. Methods: Discussions were organised with bitch owners about the practice of ovariohysterectomy and its importance for the well-being of the animals. The harvested plant was then prepared and the resulting crushed material was macerated, followed by the addition of drinking water. The subjects were divided into two batches of 6 animals: the control batch (batch 1) and the extract batch (batch 2). Before applying the macerate, the wounds were cleaned with distilled water and then an absorbent paper towel was used to dry them. Results : Application of C. asiatica macerate to post-operative wounds in female dogs showed good clinical applicability, with anti-inflammatory and wound-healing accelerating activity. The therapeutic potential of the plant is thought to be attributable to its most important bioactive components. Conclusion : The study argues that C. asiatica could be a better alternative for surgical wound closure, helping breeders to minimize intervention costs. Peer Review History: Received: 5 October 2023; Revised: 8 November; Accepted: 25 December; Available online: 15 January 2024 Academic Editor: Dr. Emmanuel O. Olorunsola , Department of Pharmaceutics & Pharmaceutical Technology, University of Uyo, Nigeria, olorunsolaeo@yahoo.com Reviewers: Dr. Adebayo Gege Grace Iyabo, University of Ibadan, Nigeria, funbimbola@gmail.com Dr. Alfonso Alexander Aguileral, University of Veracruz, Mexico, aalexander_2000@yahoo.com